A compact QRS detection system based on 0.79 μW analog CMOS energy-of-derivative circuit. (July 2021) - Silva, Rafael Sanchotene; Plantes Neto, Afonso Roberto; Marques, Jefferson Luiz Brum; Kavehei, Omid; Rodrigues, Cesar Ramos
Abstract: We propose a novel QRS detection system consisting of compact and low-power blocks: an analog energy-of-derivative operator, comparator, and a refractory period timer. The goal is to offer a mixed-signal alternative to mainstream algorithmic QRS-detection techniques reducing both the overall power consumption and silicon area in wearable or implantable ECG processing systems. Circuit design, simulations, and tests are performed with the 0.18 μm CMOS process. The system performance is evaluated by identifying QRS complexes in a set of 48 pre-filtered data stream ECG records from the MIT/BIH dataset, with classification sensitivity and precision of 97.81% and 99.71%, respectively, combined to reduced power consumption (0.79 μW) and occupy a small silicon area (0.011 mm 2 ). The main contribution is to demonstrate the feasibility of implementing QRS detection with an ultra-low-power analog energy-of-derivative circuit with performance comparable to state-of-the-art algorithmic approaches. The proposed system can be a competitive option to integrated front-ends of implantable or wearable biomedical devices.